Systematic review of health care interventions: an essential component of health sciences graduate programs. - Peacock S; Forbes D (International Journal of Nursing Education Scholarship, 2004)
Systematic reviews are an objective, rigorous assessment of both published and unpublished research that enable the reviewer to make recommendations to clinicians, policy-makers, consumers, and researchers. The steps in a systematic review include: (a) developing a research question, (b) developing relevance and validity tools, (c) conducting a thorough literature search of published and unpublished studies, (d) using relevance and validity tools to assess the studies, (e) completing data extraction for each study, (f) synthesizing the findings and, (g) writing the report. The purpose of this paper is to demonstrate the value of providing health science graduate students with the opportunity to learn about the conduct of a systematic review. An example of a thesis utilizing the method of a systematic review is presented.